2003
DOI: 10.1074/jbc.m201521200
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Domain Containing a Leucine-rich Sequence Regulates Nuclear Cytoplasmic Localization of Protein 4.1R

Abstract: In red blood cells, protein 4.1 (4.1R) is an 80-kDa protein that stabilizes the spectrin-actin network and anchors it to the plasma membrane. The picture is more complex in nucleated cells, in which many 4.1R isoforms, varying in size and intracellular location, have been identified. To contribute to the characterization of signals involved in differential intracellular localization of 4.1R, we have analyzed the role the exon 5-encoded sequence plays in 4.1R distribution. We show that exon 5 encodes a leucine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…Actin contains two nuclear export signals but no nuclear localization signal, and thus it is unclear how actin becomes nuclear. Several 4.1 family members have actinbinding domains, and 4.1R has sites regulating nuclear localization distinct from its actin-binding site (40)(41)(42). It is possible that one regulated means for actin to become nuclear is via 4.1 binding, a hypothesis to be tested in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Actin contains two nuclear export signals but no nuclear localization signal, and thus it is unclear how actin becomes nuclear. Several 4.1 family members have actinbinding domains, and 4.1R has sites regulating nuclear localization distinct from its actin-binding site (40)(41)(42). It is possible that one regulated means for actin to become nuclear is via 4.1 binding, a hypothesis to be tested in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that proteins containing an NLS often have casein kinase II sites 10 -30 amino acids from the NLS (Schmucker et al, 1999). Nuclear localization signals have also been reported for 4.1R (Correas et al, 2001;Luque et al, 2003) and NF2 (Schmucker et al, 1999).…”
Section: Identification Of Exon-intron Boundaries Of Dal-1/41bmentioning
confidence: 92%
“…(Luque and Correas, 2000;Luque et al, 1999). The 4.1R 60 ∆16,18-GFP cDNA was constructed as detailed elsewhere (Luque et al, 2003). The glutathione-S-transferase (GST), GST C-terminus (GST-Cter), 60 ∆16,18 and GST-4.1R 80 ∆16 proteins were prepared as described elsewhere (Perez-Ferreiro et al, 2001).…”
Section: Methodsmentioning
confidence: 99%